Metal oxide grafted with nitrile functional group on surface and preparation method and application thereof

By grafting nitrile functional groups on the surface of the positive electrode material of lithium-ion battery, the problem of structural instability of the material during charging and discharging is solved, the cycle stability and rate performance of the material are improved, and the safety of the battery is enhanced.

CN119673985APending Publication Date: 2025-03-21HEBEI UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410620156.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The structure of the existing lithium-ion battery positive electrode material is unstable during charging and discharging, resulting in poor capacity and voltage attenuation and rate performance, and the reaction with the electrolyte leads to a reduced safety.

Method used

The metal oxide with nitrile functional groups is grafted on the surface, and the nitrile functional groups are formed by heat treatment with hexamethylenetetramine, which is uniformly grafted on the surface of the metal oxide to form a stable surface structure.

Benefits of technology

The structural stability and cyclic stability of metal oxides are improved, metal ion dissolution is inhibited, and the rate performance and safety of the positive electrode material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673985A_ABST
    Figure CN119673985A_ABST
Patent Text Reader

Abstract

The invention discloses a metal oxide grafted with nitrile functional groups on the surface and a preparation method and application thereof.The preparation method comprises the following steps that S10, a metal compound precursor and a lithium source are evenly mixed in a mortar, the temperature of the mixture is increased to 800-900 DEG C, the mixture is naturally cooled to the room temperature, and the metal oxide is obtained; s20, weighing a metal oxide and laying the metal oxide at the bottom of the reaction kettle; s30, weighing hexamethylenetetramine, putting the hexamethylenetetramine into a beaker, and then putting the beaker into a reaction kettle containing a metal oxide; s40, the reaction kettle is sealed, a heat treatment reaction is conducted at the temperature of 200-250 DEG C, the heat treatment time is 3-12 h, and nitrile functional groups are generated in decomposition gas of hexamethylenetetramine; and S50, after the reaction is completed, cooling to room temperature, and sintering at 350-600 DEG C to obtain metal oxide powder grafted with nitrile functional groups on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to a metal oxide with nitrile functional groups grafted on the surface thereof, and a preparation method and application thereof. Background Art

[0002] At present, with the continuous development of society, energy shortage has become one of the urgent problems to be solved. Moreover, the greenhouse effect and environmental pollution caused by traditional energy that people have been using for a long time are becoming more and more serious. In order to achieve sustainable development, we must reduce dependence on traditional energy. Therefore, finding clean new energy has become one of the main tasks at present.

[0003] Lithium-ion batteries have been developing rapidly since their emergence due to their advantages such as high mass-to-volume specific energy, low pollution, excellent cycle stability and reliable safety performance. Nowadays, lithium-ion batteries have been widely used in electric vehicles, energy storage power supplies and 3C digital products, and will be widely used in advanced fields such as smart grids and large-scale energy storage systems in the future.

[0004] At present, the specific capacity of positive electrode materials of lithium-ion batteries cannot match that of negative electrode materials, which has become a decisive factor restricting the development of lithium-ion batteries. Therefore, the development of new positive electrode materials with higher specific capacity is the key to the development of lithium-ion batteries. The metal oxide positive electrode material with the general formula xLi2MnO3·(1-x)LMO2 (M=Mn, Co, Ni, Fe, etc.) has a theoretical specific capacity of more than 300mAh / g and an actual specific capacity of more than 200mAh / g. It is regarded as one of the candidates for the next generation of positive electrode materials for lithium-ion batteries and has received widespread attention from researchers. However, this type of battery material also has some disadvantages. It has a high operating voltage and is more likely to react with the electrolyte to destroy the surface structure of the material. In addition, in the completely delithiated state, the thermal stability of the material deteriorates, resulting in reduced battery safety. These problems seriously hinder the application of this type of positive electrode material in high-energy lithium-ion batteries.

[0005] The problems of capacity and voltage attenuation, poor rate performance, etc. of this type of positive electrode material are mainly caused by the structural instability and surface structure damage of this type of positive electrode material during the charge and discharge process, according to relevant experimental research and theoretical analysis. The excessively high charge cut-off voltage exceeds the electrochemical stability window of most organic electrolytes, causing the LiPF6-based electrolyte to decompose and produce acidic substances such as HF, PF5, etc., which corrode the positive electrode surface, induce metal ion dissolution, and accelerate the phase transition from layered to spinel. Therefore, during the charge and discharge process, the degradation of the material surface structure seriously affects the cycle stability of the electrode material. However, there is currently no simple and effective treatment method to improve the above defects. Summary of the invention

[0006] In response to the problems and needs raised above, this proposal proposes a metal oxide with nitrile functional groups grafted on its surface, and a preparation method and application thereof. Due to the following technical features, the above technical objectives can be achieved and many other technical effects can be brought about.

[0007] One object of the present invention is to provide a metal oxide with nitrile functional groups grafted on its surface, wherein the chemical expression of the metal oxide with nitrile functional groups grafted on its surface is xLi2MnO3·(1-x)LiMO2, wherein 0≤x≤1, and M is at least one of the metal ions of Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

[0008] In one example of the present invention, the chemical expression of the lithium-rich metal oxide is: xLi2MnO3·(1-x)LiMO2, wherein 0<x<1, and M is at least one of nine metal ions including Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

[0009] Another object of the present invention is to provide a method for preparing a metal oxide with nitrile functional groups grafted on its surface, comprising the following steps:

[0010] S10: uniformly mixing the metal compound precursor and the lithium source in a mortar, heating the mixture to 800-900° C., and naturally cooling to room temperature to obtain a metal oxide;

[0011] S20: weigh the metal oxide and spread it on the bottom of the reactor;

[0012] S30: weigh hexamethylenetetramine and put it into a beaker, and then put the beaker into a reaction kettle containing metal oxide;

[0013] S40: sealing the reaction kettle and performing a heat treatment reaction at 200-250° C. for 3-12 hours, wherein nitrile functional groups are generated in the decomposition gas of hexamethylenetetramine;

[0014] S50: After the reaction is completed, the mixture is cooled to room temperature and sintered at 350-600° C. to obtain metal oxide powder with nitrile functional groups grafted on the surface.

[0015] In an example of the present invention, in step S10, the metal compound precursor is metal carbonate or metal hydroxide microspheres.

[0016] In one example of the present invention, in step S10, the particle size of the metal carbonate or metal hydroxide microspheres is 5 to 15 μm.

[0017] In one example of the present invention, the metal carbonate is MCO3, and the metal hydroxide is M(OH)2, wherein M is at least one of nine metal ions including Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

[0018] In one example of the present invention, in step S10, the lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium acetate.

[0019] In an example of the present invention, in step S30, the mass ratio of the metal oxide to hexamethylenetetramine is 1:1-7.

[0020] In one example of the present invention, in step S50, the expression of the metal oxide with nitrile functional groups grafted on the surface is Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2.

[0021] Another object of the present invention is to propose a method for preparing a metal oxide with nitrile functional groups grafted on its surface as described above, and to apply the metal oxide with nitrile functional groups grafted on its surface, characterized in that the metal oxide with nitrile functional groups grafted on its surface is applied to the positive electrode material of a lithium-ion battery or a power battery.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The gas-solid treatment adopted in the present invention ensures that the nitrile functional groups are uniformly grafted on the surface of the metal oxide. The nitrile functional groups bond with the metal ions on the surface by virtue of their strong coordination with the transition metal ions, inhibiting the dissolution of the metal ions, thereby improving the structural stability of the metal oxide and improving the cycle stability of the metal oxide as a lithium ion positive electrode material.

[0024] 2. The surface grafting nitrile functional group modification treatment of the present invention avoids the lattice mismatch problem of the surface coating layer modification treatment during the cycle and the stringent requirements of the functional electrolyte additive modification treatment, and combines the advantages of both. By using the surface modification pretreatment method, the useful nitrile functional groups in the electrolyte additive are directly pre-grafted onto the metal oxide surface to construct a functionalized surface, thereby improving the cycle stability of the lithium ion positive electrode material.

[0025] The best embodiment for carrying out the present invention will be described in more detail below with reference to the accompanying drawings so that the features and advantages of the present invention can be easily understood. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings of the embodiments of the present invention, wherein the drawings are only used to illustrate some embodiments of the present invention, but not to limit all embodiments of the present invention thereto.

[0027] Figure 1 According to Example 1 of the present invention, Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 X-ray diffraction patterns of powders of O2 cathode material before and after treatment;

[0028] Figure 2 is Li in Example 1 1.2 Mn 0.54 Co 0.13 Ni 0.13 XPS graph of O2 cathode material before and after treatment;

[0029] Figure 3 is Li in Example 1 1.2 Mn 0.54 Co 0.13 Ni 0.13 Infrared absorption spectra of O2 cathode materials before and after treatment;

[0030] Figure 4 is Li in Example 1 1.2 Mn 0.54 Co 0.13 Ni 0.13 The cycling performance curves of the powder as the positive electrode before and after O2 positive electrode material treatment at room temperature with current densities of 40, 100, 400 and 1000 mA / g respectively. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the technical solution of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in conjunction with the drawings of specific embodiments of the present invention. The same figure marks in the drawings represent the same parts. It should be noted that the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Unless otherwise defined, the technical terms or scientific terms used herein shall have the usual meanings understood by persons of ordinary skill in the field to which the present invention belongs. The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, words such as "one" or "one" do not necessarily indicate a quantity limitation. Words such as "include" or "comprise" mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Words such as "connect" or "connected" are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0033] According to the first aspect of the present invention, a metal oxide with a nitrile functional group (-C≡N) grafted on its surface has a chemical expression of xLi2MnO3·(1-x)LiMO2, wherein 0≤x≤1, and M is at least one of the metal ions of Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

[0034] In one example of the present invention, the chemical expression of the lithium-rich metal oxide is: xLi2MnO3·(1-x)LiMO2, wherein 0<x<1, and M is at least one of nine metal ions including Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

[0035] According to the second aspect of the present invention, a method for preparing a metal oxide with nitrile functional groups grafted on its surface comprises the following steps:

[0036] S10: uniformly mixing the metal compound precursor and the lithium source in a mortar, heating the mixture to 800-900° C., and naturally cooling to room temperature to obtain a metal oxide;

[0037] S20: weigh the metal oxide and spread it on the bottom of the reactor;

[0038] S30: weigh hexamethylenetetramine and put it into a beaker, and then put the beaker into a reaction kettle containing metal oxide;

[0039] S40: sealing the reaction kettle and performing a heat treatment reaction at 200-250° C. for 3-12 hours, wherein nitrile functional groups are generated in the decomposition gas of hexamethylenetetramine;

[0040] S50: After the reaction is completed, the mixture is cooled to room temperature and sintered at 350-600° C. to obtain metal oxide powder with nitrile functional groups grafted on the surface.

[0041] The preparation method utilizes the gas generated by the thermal decomposition of hexamethylenetetramine to treat the metal oxide, and performs a gas-solid reaction on the metal oxide in a reactor to form a metal oxide with a nitrile functional group grafted on the surface, and will not affect the main layered structure of the metal oxide. The nitrile group is tightly combined with the metal ions on the surface of the metal oxide, suppressing the dissolution of the metal ions and forming a solid positive electrode-electrolyte interface framework. The treatment in the gas does not introduce other impurity ions, thereby ensuring the purity of the product. After the subsequent assembly into a battery, the side reaction with the electrolyte is suppressed, and the cycle performance of the material is greatly improved. The preparation method is simple in process, easy to control, and has good repeatability. It can be applied on a large scale. The preparation method is not limited to the material disclosed in the present invention, and can also be used for the post-treatment of other lithium ion battery positive electrode materials. The method has a large application space and has a broad application prospect.

[0042] In an example of the present invention, in step S10, the metal compound precursor is metal carbonate or metal hydroxide microspheres.

[0043] In one example of the present invention, in step S10, the particle size of the metal carbonate or metal hydroxide microspheres is 5 to 15 μm.

[0044] In one example of the present invention, the metal carbonate is MCO3, and the metal hydroxide is M(OH)2, wherein M is at least one of nine metal ions including Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

[0045] In one example of the present invention, in step S10, the lithium source is at least one of lithium carbonate, lithium hydroxide, and lithium acetate.

[0046] In an example of the present invention, in step S30, the mass ratio of the metal oxide to hexamethylenetetramine is 1:1-7.

[0047] In one example of the present invention, in step S50, the expression of the metal oxide with nitrile functional groups grafted on the surface is Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2.

[0048] According to the third aspect of the present invention, a method for preparing a metal oxide with nitrile functional groups grafted on the surface as described above is used to prepare a metal oxide with nitrile functional groups grafted on the surface, and the metal oxide with nitrile functional groups grafted on the surface is applied to a positive electrode material of a lithium ion battery or a power battery. In other words, the metal oxide with nitrile functional groups grafted on the surface is used as a positive electrode material in the field of lithium ion batteries or power batteries.

[0049] Specific examples

[0050] Example 1: Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2 cathode material post-processing

[0051] 0.02 mol of metal carbonate (Mn 0.6 Co 0.2 Ni 0.2 CO3) or metal hydroxide precursors (Mn 0.6 Co 0.2 Ni 0.2 (OH)2) was mixed with an excess of lithium carbonate or lithium hydroxide, and the mixture was placed in a muffle furnace, heated to 850°C at a rate of 5°C / min and kept at this temperature for 12 hours, and then naturally cooled to room temperature to obtain an untreated sample, namely a metal oxide (Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2). Weigh 1g Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 The O2 positive electrode material powder was placed in a 100 ml reactor; 1 g of hexamethylenetetramine was placed in a 10 ml flask and placed in the reactor; the sealed reactor was taken out and placed in a 215°C oven for 12 hours; after cooling, the powder was sintered at 350°C to obtain Li+ with surface grafted nitrile functional groups. 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2 material. Figure 1 This is the X-ray diffraction pattern of the sample powder before and after treatment. The structure and composition of the positive electrode material can be seen from the figure. Figure 2 XPS images of samples before and after treatment. Figure 3The infrared absorption spectra of the samples before and after treatment. It is known that there are nitrile groups. The electrochemical performance test was carried out using button cells. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 8:1:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After mixing into a slurry, it was evenly coated on aluminum foil and dried in vacuum at 100°C to obtain the electrode. The metal lithium sheet was used as the counter electrode, and 1 mol·L -1 LiPF6 / EC+DMC+EMC (volume ratio 1:1:1) was used as the electrolyte and polypropylene material was used as the diaphragm. 2025 button cells were assembled in a glove box filled with argon. A NEWARE TC53 battery test system was used to perform charge and discharge tests at a constant current density. The charge and discharge voltage range was 2.0 to 4.8 V, and the charge and discharge current densities were 40, 100, 400, and 1000 mA / g, respectively. Figure 4 The cycle characteristic curve obtained for the test shows that the capacity of the positive electrode material before material treatment after cycling at different current densities is 210.5mAh / g, 182.2mAh / g, 144.1mAh / g, and 128.4mAh / g, respectively. The capacity of the positive electrode material after treatment after cycling at different current densities is 244.7mAh / g, 224.8mAh / g, 193.2mAh / g, and 173.2mAh / g, respectively. The material with surface grafted nitrile functional groups exhibits excellent cycle performance and rate performance.

[0052] Example 2: Li 1.2 Mn 0.4 Co 0.4 O2 cathode material post-processing

[0053] 0.02 mol of metal carbonate (Mn 0.5 Co 0.5 CO3) or metal hydroxide precursors (Mn 0.5 Co 0.5 (OH)2) was mixed with an excess of lithium carbonate or lithium hydroxide, and the mixture was placed in a muffle furnace, heated to 800°C at a rate of 5°C / min and kept at this temperature for 12 hours, and then naturally cooled to room temperature to obtain an untreated sample, namely a metal oxide (Li 1.2 Mn 0.4 Co 0.4 O2). Weigh 1g Li 1.2 Mn 0.4 Co 0.4 The O2 positive electrode material powder was placed in a 100 ml reactor; 3 g of hexamethylenetetramine was placed in a 10 ml flask and placed in the reactor; the sealed reactor was taken out and placed in a 200 ° C oven for 9 hours; after cooling, the powder was sintered at 500 ° C to obtain Li ions with surface grafted nitrile functional groups. 1.2 Mn0.4 Co 0.4 O2 material. The XRD test results of the powder material showed that the sample structure and composition did not change before and after the treatment. The XPS test results of the powder material showed that the sample contained nitrile groups. The electrochemical performance test was carried out using a button cell. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 8:1:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After mixing into a slurry, it was evenly coated on an aluminum foil and vacuum dried at 100°C to obtain a pole piece. A metal lithium sheet was used as the counter electrode, and 1 mol·L -1 LiPF6 / EC+DMC+EMC (volume ratio 1:1:1) was used as the electrolyte, and polypropylene material was used as the diaphragm. The 2025 button cell was assembled in a glove box filled with argon. A NEWARE TC53 battery test system was used to perform charge and discharge tests at a constant current density. The charge and discharge voltage range was 2.0-4.8V, and the charge and discharge current densities were 20, 100, 400, and 1000mA / g, respectively. At charge and discharge currents of 20, 100, 400, and 1000mA / g, the capacities of the untreated positive electrode material after charge and discharge (20mA / g cycle 40 times, 100mA / g cycle 100 times, 200mA / g cycle 200 times, 1000mA / g cycle 300 times) were 229.2mAh / g, 185.4mAh / g, 69.5mAh / g, and 45.8mAh / g, respectively. The capacities of the treated cathode materials after cycling at different current densities were 239.8 mAh / g, 212.6 mAh / g, 163.5 mAh / g, and 132.2 mAh / g, respectively. The materials with surface grafted nitrile functional groups showed excellent cycling performance and rate performance.

[0054] Example 3: Li 1.2 Mn 0.6 Ni 0.2 O2 cathode material post-processing

[0055] 0.02 mol of metal carbonate (Mn 3 / 4 Ni 1 / 4 CO3) or metal hydroxide precursors (Mn 3 / 4 Ni 1 / 4 (OH)2) was mixed evenly with an excess of lithium carbonate or lithium hydroxide, and the mixture was placed in a muffle furnace, heated to 900°C at a rate of 5°C / min and kept at this temperature for 12 hours, and then naturally cooled to room temperature to obtain an untreated sample, namely a metal oxide (Li 1.2 Mn 0.6 Ni 0.2 O2). Weigh 1g Li 1.2 Mn 0.6 Ni 0.2The O2 positive electrode material powder was placed in a 100 ml reactor; 7 g of hexamethylenetetramine was placed in a 10 ml flask and placed in the reactor; the sealed reactor was taken out and placed in a 250°C oven for 3 hours; after cooling, the powder was sintered at 600°C to obtain Li+ with surface grafted nitrile functional groups. 1.2 Mn 0.6 Ni 0.2 O2 material. The XRD test results of the powder material showed that the sample structure and composition did not change before and after the treatment. The XPS test results of the powder material showed that the sample contained nitrile groups. The electrochemical performance test was carried out using a button cell. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 8:1:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After mixing into a slurry, it was evenly coated on an aluminum foil and vacuum dried at 100°C to obtain a pole piece. A metal lithium sheet was used as the counter electrode, and 1 mol·L -1 LiPF6 / PC+DEC+EMC (volume ratio 3:2:1) was used as the electrolyte, and polypropylene material was used as the diaphragm. The 2025 button cell was assembled in a glove box filled with argon. The NEWARE TC53 battery test system was used to perform charge and discharge tests at a constant current density. The charge and discharge voltage range was 2.0-4.8V, and the charge and discharge current densities were 20, 100, 400, and 1000mA / g, respectively. At charge and discharge currents of 20, 100, 400, and 1000mA / g, the capacities of the untreated positive electrode material after charge and discharge cycles (20mA / g cycle 40 times, 100mA / g cycle 100 times, 200mA / g cycle 200 times, 1000mA / g cycle 300 times) were 227.3mAh / g, 187.1mAh / g, 108.5mAh / g, and 54.2mAh / g, respectively. The treated cathode material has a capacity of 242.5 mAh / g, 228.5 mAh / g, 157.6 mAh / g, and 112.2 mAh / g after cycling at different current densities. The material with nitrile functional groups grafted on the surface shows excellent cycle performance and rate performance.

[0056] Example 4: LiMn 1 / 3 Co 1 / 3 Ni 1 / 3 O2 cathode material

[0057] 0.02 mol of metal carbonate (Mn 0.6 Co 0.2 Ni 0.2 CO3) or metal hydroxide precursors (Mn 0.6 Co 0.2 Ni 0.2(OH)2) was mixed evenly with lithium carbonate or lithium hydroxide in a certain stoichiometric ratio, and the mixture was placed in a muffle furnace, heated to 850°C at a rate of 5°C / min and kept at this temperature for 12 hours, and then naturally cooled to room temperature to obtain an untreated sample, namely a metal oxide (LiMn 1 / 3 Co 1 / 3 Ni 1 / 3 O2). Weigh 1g LiMn 1 / 3 Co 1 / 3 Ni 1 / 3 The O2 positive electrode material powder was placed in a 100 ml reactor; 4 g of hexamethylenetetramine was placed in a 10 ml flask and placed in the reactor; the sealed reactor was taken out and placed in a 220°C oven for 8 hours; after cooling, the powder was sintered at 500°C to obtain LiMn with nitrile functional groups grafted on the surface. 1 / 3 Co 1 / 3 Ni 1 / 3 O2 material. The XRD test results of the powder material showed that the sample structure and composition did not change before and after the treatment. The XPS test results of the powder material showed that the sample contained nitrile groups. The electrochemical performance test was carried out using a button cell. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 8:1:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After mixing into a slurry, it was evenly coated on an aluminum foil and vacuum dried at 100°C to obtain a pole piece. A metal lithium sheet was used as the counter electrode, and 1 mol·L -1 LiPF6 / EC+DMC+EMC (volume ratio 1:1:1) was used as the electrolyte, and polypropylene material was used as the diaphragm. The 2025 button cell was assembled in a glove box filled with argon. The charge and discharge test was carried out at a constant current density using a NEWARE TC53 battery test system. The charge and discharge voltage range was 2.5-4.5V, and the charge and discharge current density was selected as 20, 100, 400, and 1000mA / g. At the charge and discharge current of 20, 100, 400, and 1000mA / g, the capacity of the untreated positive electrode material after charge and discharge cycles (20mA / g cycle 40 times, 100mA / g cycle 100 times, 200mA / g cycle 200 times, 1000mA / g cycle 300 times) was 159.3mAh / g, 102mAh / g, 53.2mAh / g, and 22.9mAh / g, respectively. The treated cathode materials have capacities of 170.5 mAh / g, 144.5 mAh / g, 107.7 mAh / g, and 52.2 mAh / g respectively after cycling at different current densities. The materials with surface grafted nitrile functional groups show excellent cycle performance and rate performance.

[0058] Example 5: LiNi 0.8 Mn 0.1 Co 0.1O2 cathode material

[0059] 0.02 mol of metal carbonate (Mn 0.6 Co 0.2 Ni 0.2 CO3) or metal hydroxide precursors (Mn 0.6 Co 0.2 Ni 0.2 (OH)2) was mixed evenly with lithium carbonate or lithium hydroxide in a certain stoichiometric ratio, and the mixture was placed in a muffle furnace, heated to 900°C at a rate of 5°C / min and kept at this temperature for 12 hours, and then naturally cooled to room temperature to obtain an untreated sample, namely a metal oxide (LiNi 0.8 Mn 0.1 Co 0.1 O2). Weigh 1g LiNi 0.8 Mn 0.1 Co 0.1 The O2 positive electrode material powder was placed in a 100 ml reactor; 5 g of hexamethylenetetramine was placed in a 10 ml flask and placed in the reactor; the sealed reactor was taken out and placed in a 240°C oven for 12 hours; after cooling, the powder was sintered at 500°C to obtain LiNi with surface grafted nitrile functional groups. 0.8 Mn 0.1 Co 0.1 O2 material. The XRD test results of the powder material showed that the sample structure and composition did not change before and after the treatment. The XPS test results of the powder material showed that the sample contained nitrile groups. The electrochemical performance test was carried out using a button cell. The sample, conductive carbon black and binder (polyvinylidene fluoride) were mixed in a mass ratio of 8:1:1, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added. After mixing into a slurry, it was evenly coated on an aluminum foil and vacuum dried at 100°C to obtain a pole piece. A metal lithium sheet was used as the counter electrode, and 1 mol·L -1LiPF6 / EC+DMC+EMC (volume ratio 1:1:1) was used as the electrolyte, and polypropylene material was used as the diaphragm. The 2025 button cell was assembled in a glove box filled with argon. The charge and discharge test was carried out at a constant current density using a NEWARE TC53 battery test system. The charge and discharge voltage range was 3.0-4.3V, and the charge and discharge current densities were 20, 100, 400, and 1000mA / g, respectively. At charge and discharge currents of 20, 100, 400, and 1000mA / g, the untreated positive electrode material had a capacity of 148.9mAh / g, 126.5mAh / g, 82.3mAh / g, and 61.9mAh / g after 100 cycles of charge and discharge (40 cycles at 20mA / g, 100 cycles at 100mA / g, 200 cycles at 200mA / g, and 300 cycles at 1000mA / g), respectively. The positive electrode material with surface grafted nitrile functional groups has a capacity of 178.5 mAh / g, 132.5 mAh / g, 127.6 mAh / g, and 100.3 mAh / g after 100 cycles at different current densities. The treated material shows excellent cycle performance and rate performance.

[0060] The exemplary embodiments of the metal oxide with nitrile functional groups grafted on the surface and the preparation method and application thereof proposed in the present invention are described in detail with reference to the preferred embodiments. However, it can be understood by those skilled in the art that, without departing from the concept of the present invention, various modifications and variations can be made to the above-mentioned specific embodiments, and various technical features and structures proposed in the present invention can be combined in various ways without exceeding the protection scope of the present invention, which is determined by the attached claims.

Claims

1. A metal oxide with nitrile functional groups grafted onto its surface, characterized in that: The chemical expression of the metal oxide is xLi2MnO3·(1-x)LiMO2, wherein 0≤x≤1, and M is at least one of nine metal ions including Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

2. The metal oxide with nitrile functional groups grafted onto its surface according to claim 1, characterized in that: The chemical expression of lithium-rich metal oxide is: xLi2MnO3·(1-x)LiMO2, where 0<x<1, and M is at least one of nine metal ions including Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

3. A method for preparing a metal oxide with nitrile functional groups grafted onto its surface, characterized in that: The steps include: S10: uniformly mixing the metal compound precursor and the lithium source in a mortar, heating the mixture to 800-900° C., and naturally cooling to room temperature to obtain a metal oxide; S20: weigh the metal oxide and spread it on the bottom of the reactor; S30: weigh hexamethylenetetramine and put it into a beaker, and then put the beaker into a reaction kettle containing metal oxide; S40: sealing the reaction kettle and performing a heat treatment reaction at 200-250° C. for 3-12 hours, wherein nitrile functional groups are generated in the decomposition gas of hexamethylenetetramine; S50: After the reaction is completed, the mixture is cooled to room temperature and sintered at 350-600° C. to obtain metal oxide powder with nitrile functional groups grafted on the surface.

4. The method for preparing a metal oxide with nitrile functional groups grafted onto its surface according to claim 3, characterized in that: In step S10, the metal compound precursor is metal carbonate or metal hydroxide microspheres.

5. The method for preparing a metal oxide with nitrile functional groups grafted onto its surface according to claim 4, characterized in that: In step S10, the particle size of the metal carbonate or metal hydroxide microspheres is 5 to 15 μm.

6. The method for preparing a metal oxide with nitrile functional groups grafted onto its surface according to claim 4, characterized in that: The metal carbonate is MCO3, and the metal hydroxide is M(OH)2, wherein M is at least one of nine metal ions including Mn, Co, Ni, Fe, Cr, Nb, La, Zr, and Mo.

7. The method for preparing a metal oxide with nitrile functional groups grafted onto its surface according to claim 3, characterized in that: In step S10, the lithium source is at least one of lithium carbonate, lithium hydroxide and lithium acetate.

8. The method for preparing a metal oxide with nitrile functional groups grafted onto its surface according to claim 3, characterized in that: In step S30, the mass ratio of the metal oxide to hexamethylenetetramine is 1:1-7.

9. The method for preparing a metal oxide with nitrile functional groups grafted onto its surface according to claim 3, characterized in that: In the step S50, the metal oxide with nitrile functional groups grafted on the surface is represented by Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2.

10. A method for preparing a metal oxide with nitrile functional groups grafted onto its surface as claimed in any one of claims 3 to 9, wherein the method comprises: Metal oxides with nitrile functional groups grafted on their surfaces are used as positive electrode materials for lithium-ion batteries or power batteries.

Citation Information

Patent Citations

  • Lithium ion battery positive electrode material surface post-treatment method

    CN110896142A

  • Lithium ion battery positive electrode material and doping method thereof

    CN115440971A

  • Graft copolymer and use thereof

    US20220135723A1

  • Composition, positive electrode composition, positive electrode slurry, positive electrode, and secondary battery

    US20230275233A1